Confocal laser scanning microscope analysis on post-biofilm assessment of biofilmproducing osteomyelitic staphylococcus aureus treated with new gentamicin-nigella sativa fusion emulsion (GNFE) - Yaacob, Khairul Ikhwan; Mohd Shafri, Mohd Affendi; Mohd Yusof, Nazri; Mohamed, Farahidah (Microscopy Society of Malaysia (MSM), 2015)
Biofilm complicates osteomyelitis as there is antibiotic resistance and toxicity involved. In order to overcome the challenges of current treatment, gentamicin, the current antibiotic of choice for osteomyelitis, is fused with Nigella sativa oil to form an emulsion. Its efficacy as anti-biofilm agent is assessed using confocal laser scanning microscope (CLSM) against different strains of biofilm-producing Staphylococcus aureus. These strains of S.aureus were first allowed to express biofilm before being exposed for 24 hours to the emulsion with (0.1% (w/v) gentamicin; 40.2% (v/v) N.sativa. Later, the emulsion was removed and the biofilm was stained with fluorescence staining. The slides were viewed under CLSM at 100 times resolution. 3D images of biofilm were reconstructed, using Image J software, to measure the thickness of biofilm and viability of bacteria cells. Results revealed that the emulsion significantly reduced biofilm thickness compared to gentamicin and N.sativa alone in all strains of S.aureus (Tukey’s test p < 0.05). The emulsion was also able to produce more than 80% and 15% surface percentage (%) of non-viable (dead) bacteria in the sensitive and resistant strain, respectively, at a significant level when compared to gentamicin and N.sativa (Tukey’s test p < 0.05). As a conclusion, this new fusion of gentamicin-N.sativa may be effective towards the biofilm of S.aureus, and can be developed further as a new promising anti-biofilm agent in osteomyelitis.